2020
DOI: 10.1101/2020.06.27.175273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated Neurokinin 1-Receptor Expression in uterine products of conception is associated with first trimester Miscarriages

Abstract: AbstractBackgroundMiscarriage is a common complication of early pregnancy, mostly occurring in first trimester. However, the etiological factors, prognostic and diagnostic biomarkers are not well known. Neurokinin-1 Receptor (NK-1R) is a receptor of tachykinin peptide, Substance P (SP) and has a role in various pathological conditions, cancers but it’s association with miscarriages and significance as a clinicopathological parameter is not stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…20 Previous studies from our own work have also revealed the involvement of SP and NK-1R in cardiorespiratory control 21 , sleep wake cycle 21 , inflammation 22 and involvement in fatal outcomes 17 . Some of our recent unpublished work also reports similar findings of SP/NK-1R involvement in inflammation 23 , pain, pathologies, sudden deaths 24 etc. SP and NK-1R are also found to be involved in immunology 7, 15 , lung inflammation 2, 7 , respiratory network stability 25, 26 , heart failure 27 and neurological and psychiatric disorders 28 .…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…20 Previous studies from our own work have also revealed the involvement of SP and NK-1R in cardiorespiratory control 21 , sleep wake cycle 21 , inflammation 22 and involvement in fatal outcomes 17 . Some of our recent unpublished work also reports similar findings of SP/NK-1R involvement in inflammation 23 , pain, pathologies, sudden deaths 24 etc. SP and NK-1R are also found to be involved in immunology 7, 15 , lung inflammation 2, 7 , respiratory network stability 25, 26 , heart failure 27 and neurological and psychiatric disorders 28 .…”
Section: Introductionsupporting
confidence: 67%
“…In our recent study, we have also suggested the similar role for aprepitant. 24 It may also improve the respiratory conditions in pre-mature labour as well as Covid-19 patients. We also suggest Ondansetron, a serotonin receptor antagonist along with these two drugs.…”
Section: Discussionmentioning
confidence: 99%